Planning and Development of Disaster-Resilient Tourism at Parangtritis Beach, Yogyakarta: Integrating Landscape Hazard Aspects and Tourist Attractions - Mulyadi Alwi; Muhammad Rizal Pahleviannur (Jurnal Lingkungan Kebumian Indonesia, 2025)
This study formulates strategies for planning and developing disaster-resilient tourism at Parangtritis Beach, Bantul Regency, Yogyakarta, by integrating landscape-hazard considerations with tourist attractions. The area possesses substantial tourism potential, but is highly vulnerable to natural hazards, particularly earthquakes and tsunamis, due to its proximity to active subduction zones. A personal judgment method was employed using checklist sheets based on disaster preparedness parameters, including evacuation signage, building configuration, evacuation route conditions, and the availability of designated assembly points. The collected data were analyzed using a descriptive qualitative approach supported by photographic documentation. The findings indicate that Parangtritis Beach is equipped with several disaster-preparedness components, including evacuation signage, evacuation routes, and an early warning system (EWS). However, the evacuation routes remain in moderate condition and require improvement to ensure effective accessibility during emergencies. Furthermore, the existing building configurations within the tourism area have not been optimized to mitigate earthquake and tsunami risks, particularly with respect to their potential function as vertical evacuation facilities. Community involvement in disaster preparedness training also remains limited and should be strengthened to enhance mitigation effectiveness. Despite its status as a major tourist destination, Parangtritis Beach requires more comprehensive infrastructure development and preparedness measures. Therefore, this study recommends improving the quality of evacuation routes, conducting periodic building safety audits, and implementing regular disaster-preparedness training for both local communities and visitors to support the development of a safe and sustainable tourism destination in hazard-prone coastal areas.